Autonomous decision-making method for ship maneuvering in complex waters of estuarine multi-class ships routeing system - HE Yixiong; ZHANG Huwei; LIU Jiaorun; ZHAO Xingya; XIANG Shouyuan; WANG Bing (Xibei Gongye Daxue Xuebao)
In order to solve the autonomous decision-making for ship manoeuvring in complex waters of estuarine multi-class ships routeing system, key scientific issues such as digital environment, navigation rule integration, ship manoeuvrability constraints, and collision avoidance mechanism under special waters were investigated by taking the waters from the mouth of Liu River to the North Trough as an example. The requirements of analytical rules were summarized and quantified in the digital traffic environment. The collision avoidance mechanism under the constraints of ship behavioural characteristics in such waters was explored by combining the control and process prediction methods with nonlinear ship manoeuvring characteristics. Then, a feasible heading speed finding method was established, and a ship manoeuvring autonomy decision-making method under the constraints of multifactors that can dynamically adapt to the system's residual error and the target ship's random motion was proposed. Under the preset scenarios, the ship can pass safely at 0, 38, 1 184, 1 537, 2 166, 3 678, 3 808 s by altering course 4° to starboard side, decelerating, altering course 5° to starboard and decelerating, decelerating, altering course 3° to port side accelerating, altering course 3° to starboard and decelerating, decelerating, respectively. The experiments show that the present method can safely avoid the collision in the complex environment and track the course in time.